SLP-educator classroom collaboration: A review to inform reason-based practice. (January 2017) - Archibald, Lisa MD
Background and aims: Increasingly, speech language pathologists are engaging in collaborative classroom services with teachers and other educators to support children with developmental language disorder and other communication impairments. Recent systematic reviews have provided a summary of only a small fraction of the available evidence and recommended the use of reason-based practice in the absence of a sufficient empirically driven evidence base. The purpose of this paper was to provide a broad (but critical) review of the existing evidence. Main contribution: Papers were gathered through review of reference lists in the recent systematic reviews and other published works, as well as general internet searches. A total of 49 papers were identified either reporting empirical evidence pertaining to SLP-educator collaborative classroom activities, empirical evidence pertaining to consultative services, classroom instruction, or small group intervention in the classroom, or providing information, discussion, surveys, or reviews related to the topic. Evidence pertaining to vocabulary, oral language, phonological awareness, curriculum-based language, and written language were summarized together with qualifications based on elements of the research design. Conclusion and implications: Although much of the evidence must be interpreted with considerable caution, the present review is informative for clinicians looking to adopt a reason-based approach to practice.